Advergaming: Application of Knowledge in the Process of the Competitive Advantage Improvement - Mráček, Pavel; Mucha, Martin (Vysoké učení technické v Brně, Fakulta podnikatelská, 2011)
Purpose of the article The paper is involved in the utilization of the knowledge in the process of the competitive advantage improvement by means of the perspective marketing tool - advergaming. The objective of the article is the informing on the possibilities of the use of the knowledge in the field of the advergaming as the possible tool in the marketing communication, leading to the improvement of the competitive advantage of the companies. Scientific aim Research objective was to identify how knowledge management is used in the Czech companies with respect to their size. Specific aspect of our research was an influence of knowledge management on a decision making process. On the base of results we have identified the requirement of usage of knowledge management in the area of advertgaming. We argue that this is a possible approach improving competitiveness of companies. Methodology/methods Data for this paper are the data from the research carried out in the Czech companies. This survey focuses on the share of the application of the knowledge management in surveyed companies. 265 companies from the whole Czech Republic, various segments and industries, starting with the tourism, building industry, hotel industry, transport and ending with the manufacturing and distribution of the detergents and the distribution of the medical materials, were involved in the research. The companies were selected randomly. The necessary data were collected from the total number of 265 companies by means of the questionnaire research, and in certain cases the structured interview was used. The synthesis from the individual parts was made, on the basis of which the following conclusions were based. Findings The paper identifies the method of the use of the knowledge in the advergaming as a possible starting point for the potential model of the utilization of the knowledge in the marketing communication. Conclusions (limits, implications etc) For the improvement of the competitiveness of companies we recommend using of the advergaming for the promotion of both product and company itself. Either in the form of the embedment of the advertising billboard, advertising wallpaper (photograph or any other key element identifying the product or form) in the game background or the building of the puzzle, or embedding of the plot of the game into the realistic environment transferred into the electronic form (downhill skiing, car races etc.). Nevertheless, strong emphasis should be placed on the attractiveness and playability of the game itself so as to guarantee the positive perception of the advertising message of the product or company, which should influence the behavior of the receiver of the message, thereby the promotion would meet its purpose. The competitive advantage then depends on the level of the utilization and the level of concinnity of the knowledge management in the individual companies and its correct application into the advertising game. The theoretical model, proposed by the authors, should serve in the company practice as the support of the decision making process in the fields of the strategic marketing and knowledge management. The application of the model should represent the competitive advantage.
Keywords: advergaming; competitiveness; competitive advantage; In-Game-Advertising; Knowledge